Experiences of leadership in health care in sub-Saharan Africa - Curry Leslie; Taylor Lauren; Chen Peggy; Bradley Elizabeth (BMC, 2012)
Abstract Background Leadership is widely regarded as central to effective health-care systems, and resources are increasingly devoted to the cultivation of strong health-care leadership. Nevertheless, the literature regarding leadership capacity building has been developed primarily in the context of high-income settings. Less research has been done on leadership in low-income settings, including sub-Saharan Africa, particularly in health care, with attention to historical, political and sociocultural context. We sought to characterize the experiences of individuals in key health-care leadership roles in sub-Saharan Africa. Methods We conducted a qualitative study using in-person interviews with individuals (n = 17) in health-care leadership roles in four countries in sub-Saharan Africa: the Federal Democratic Republic of Ethiopia, the Republic of Ghana, the Republic of Liberia and the Republic of Rwanda. Individuals were identified by their country's minister of health as key leaders in the health sector and were nominated to serve as delegates to a global health leadership conference in June 2010, at Yale University in the United States. Interviews were audio recorded and professionally transcribed. Data analysis was performed by a five-person multidisciplinary team using the constant comparative method, facilitated by ATLAS.ti 5.0 software. Results Five key themes emerged as important to participants in their leadership roles: having an aspirational, value-based vision for improving the future health of the country, being self-aware and having the ability to identify and use complementary skills of others, tending to relationships, using data in decision making, and sustaining a commitment to learning. Conclusions Current models of leadership capacity building address the need for core technical and management competencies. While these competencies are important, skills relevant to managing relationships are also critical in the sub-Saharan African context. Developing such skills may require more time and a deeper level of engagement and collaboration than is typically invested in efforts to strengthen health systems.